Naringenin complexes with copper ions: potentiometric studies - Brodowska, Katarzyna (Biotechnology and Food Science, 2013)
Flavanones belong to the group of active flavonoid compounds, rarely occurring in the plant kingdom and are found in many foodstuffs (naringenin and derivatives) and medicinal plant materials. Many studies have demonstrated a relationship between dietary intake of phenolic compounds and reduced risk of cancer and cardiovascular disease. Accordingly, during over several years, flavonoids have gained increasing interest and numerous studies have shown that they possess beneficial properties having a great influence on human health. Acid dissociation constants are believed to be the most useful physico-chemical parameters which describe the extent of ionization of functional groups as a function of pH. It is very important in research areas such as pharmaceutical drug discovery and development due to vital role in understanding the pharmacodynamic properties of new drug substances. Flavonoids are characterized by insolubility in water while they are soluble in organic solvents. Exploiting mixed solvents, especially organic solvent – water mixtures, enables a good alternative for researching on compounds which are inconspicuously soluble or insoluble in water. In this study the dissociation constant of naringenin and its complex with Cu(II) have been determined in aqueous – DMSO solvent mixtures to examine the dependence of their acid-base equilibria on number of substrates.